2011
DOI: 10.1364/ol.36.004401
|View full text |Cite
|
Sign up to set email alerts
|

50 dB parametric on-chip gain in silicon photonic wires

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX; posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXX A pulsed mid-infrared pump at λ = 2173 nm is used to demonstrate wideband optical parametric gain in a low-loss 2-cm long silicon photonic wire. Using dispersion engineering to obtain negative second-order (β 2 ) and positive fourth-order (β 4 ) dispersion, we generate broadband modulation instability and parametric fluorescence extending from 1911 nm -2486 nm. Using a cw probe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…For semi-standard SOI with 220-nm Si layer thickness, the optimal width for a Si waveguide operating near 2.1-μm wavelength was identified to be 900 nm, where, fortuitously, the second-order and fourth-order dispersion coefficients have opposite signs to facilitate broadband phase matching [101]. Using such waveguides, Kuyken et al [102] measured optical parametric amplification (OPA) with 550-nm net gain bandwidth (centered at 2.17-μm pump wavelength) and an impressive 30-dB Raman-assisted peak off-chip gain (with FWM contribution exceeding 20 dB). Both metrics represent major improvements over the initial on-chip mid-IR OPA demonstration by the same group where a non-optimized waveguide design was used [103].…”
Section: Nonlinear Frequency Generation or Conversionmentioning
confidence: 99%
“…For semi-standard SOI with 220-nm Si layer thickness, the optimal width for a Si waveguide operating near 2.1-μm wavelength was identified to be 900 nm, where, fortuitously, the second-order and fourth-order dispersion coefficients have opposite signs to facilitate broadband phase matching [101]. Using such waveguides, Kuyken et al [102] measured optical parametric amplification (OPA) with 550-nm net gain bandwidth (centered at 2.17-μm pump wavelength) and an impressive 30-dB Raman-assisted peak off-chip gain (with FWM contribution exceeding 20 dB). Both metrics represent major improvements over the initial on-chip mid-IR OPA demonstration by the same group where a non-optimized waveguide design was used [103].…”
Section: Nonlinear Frequency Generation or Conversionmentioning
confidence: 99%
“…Depending on the signs of β 2 and β 4 , a variety of phase matching conditions near to and far away from the pump can be obtained. In our previous work [6][7][8]13], anomalously dispersive waveguides (β 2 < 0) with a positive β 4 were used, such that phase matching both close to the pump (broadband phase matching) and …”
mentioning
confidence: 99%
“…Efficient nonlinear optical effects on the silicon photonic platform, making use of the instantaneous thirdorder χ(3) nonlinear effect, can provide a solution to many of these challenges. Recent work has shown that fourwave mixing-based nonlinear optical functions including supercontinuum generation [6], optical parametric amplification [7,8] and wavelength conversion [7][8][9][10] can be integrated for mid-infrared light generation within compact silicon photonic integrated circuits. Moreover, silicon waveguides accomplishing bi-directional broadband spectral translation of optical signals between 1620 nm and 2440 nm in the mid-infrared [11], and between 1312 nm and 1884 nm in the short-wave infrared [12] have been demonstrated using four-wave mixing phase matched by anomalous dispersion.…”
mentioning
confidence: 99%
See 2 more Smart Citations